Use of ornamental stone processing sludge in flexible pavements (Research, Society and Development, 2022)
The objective of this study is to evaluate the incorporation of sludge from the processing of ornamental rocks, as a filling material, through partial replacements of conventional materials, in hot machined bituminous concrete. The physical-chemical characteristics of the residue and other aggregates that make up the asphalt mixture were investigated, followed by the development of formulations to perform the mechanical resistance test using the Marshall method. The results show that the replacement of natural materials by waste ornamental rocks slightly improves the physical and mechanical properties of bituminous mixtures. It was therefore concluded that the slurry from ornamental stone processing has potential for use and can be a promising material to be used by the paving industry. Added to this is the fact that consumption of non-renewable natural resources is reduced, since fewer conventional raw materials can be replaced by this waste, thus avoiding mineral extraction.